Analysis of the Effect of Remuneration on Performance of Civil Servants at Lampung Agriculture Training Center - Firmansyah Yunialfi Alfian; Ario Pratama (Prosiding International conference on Information Technology and Business (ICITB), 2017)
This Research was done at Lampung Agricultural Training Center as one of UPT under Agriculture Ministry and done the birocration reformation program that was remuneration given to employees. It was hoped that employees performance would increase. The aim of this study was to know and analyze the effect of Remuneration on Civil Servants Performance at Lampung Agricultural Training  Center.  The  sample  taking  technique  used  was  saturated  sampling technique and used all population as the sample as 67 respondents. The data collecting  method  used  was  questionnaire.  The  independent  variable  was Remuneration and the dependent variable was Employee Performance. The data analysis  included  validity  test,  reliability  test,  classical  assumption  test  and hypothesis test. The analysis result shows that Remuneration positively affected the Employee Performance. Keywords :Remuneration, and Employees Performance.